Effect of Combined Treatment With Folic Acid, Vitamin B6, and Vitamin B12 on Plasma Biomarkers of Inflammation and Endothelial Dysfunction in Women. Issue 11 (18th May 2018) - Christen, William G.; Cook, Nancy R.; Van Denburgh, Martin; Zaharris, Elaine; Albert, Christine M.; Manson, JoAnn E.
Abstract : Background: The aim of this study was to determine whether reducing plasma homocysteine concentrations with long‐term, combined treatment with folic acid, vitamin B6, and vitamin B12 alters plasma biomarkers of inflammation and endothelial dysfunction in women at increased risk of cardiovascular disease. Methods and Results: We conducted a blood substudy of 300 treatment‐adherent participants (150 in the active treatment group, 150 in the placebo group) in the WAFACS (Women's Antioxidant and Folic Acid Cardiovascular Study), a randomized, double‐blind, placebo‐controlled trial testing a daily combination of folic acid (2.5 mg), vitamin B6 (50 mg), vitamin B12 (1 mg), or matching placebo, in cardiovascular disease prevention among women at increased risk of cardiovascular disease. Plasma concentration of 3 biomarkers of inflammation (C‐reactive protein, interleukin‐6, and fibrinogen) and a biomarker of endothelial dysfunction (intercellular adhesion molecule 1) were measured at baseline and at the end of treatment and follow‐up. After 7.3 years of combined treatment with folic acid, vitamin B6, and vitamin B12, homocysteine concentrations were reduced by 18% in the active treatment group as compared with the placebo group ( P <0.001). However, there was no difference between treatment groups in change in blood concentration from baseline to follow‐up for C‐reactive protein ( P =0.77), interleukin‐6 ( P =0.91), intercellular adhesion molecule 1 ( P =0.38), or fibrinogen ( P =0.68). Conclusions: These findings indicate that long‐term, combined treatment with folic acid, vitamin B6, and vitamin B12 lowers homocysteine concentrations, but does not alter major biomarkers of vascular inflammation, consistent with the lack of clinical cardiovascular disease benefit in the trial. Clinical Trial Registration: URL: http://www.clinicaltrials.gov . Unique identifier: NCT00000541.